IMPROVING THE QUALITY OF LIFE OF THE ELDERLY AT BAN LAM NAO SUBDISTRICT ADMINISTRATIVE ORGANIZATION, BANG KHAN DISTRICT, NAKHON SI THAMMARAT PROVINCE - Petruentong, Onuma; Piyaweero (Asim), Phramaha Ekkawin (Journal of MCU Nakhondhat, 2024)
This research article aims to study 1) The development of the quality of life of the elderly of the Ban Lam Nao Subdistrict Administrative Organization and 2) The promotion guidelines for the development of the quality of life of the elderly of the Ban Lam Nao Subdistrict Administrative Organization, Bang Khan District, Province. Nakhon Si Thammarat It is a mixed methods research. The sample group consisted of 322 elderly people of the Ban Lam Nao Subdistrict Administrative Organization. The sample group was selected using Krejsi and Morgan’s ready-made tables. Key informants include the elderly of the Ban Lam Nao Subdistrict Administrative Organization. Select a purposive sampling, totaling 15 people. Research tools include mean, standard deviation. collect data with questionnaire and in-depth interviews The results of the research found that: 1) Development of the quality of life of the elderly of the Ban Lam Nao Subdistrict Administrative Organization in all 4 areas overall had a high average level. When considering each aspect by The physical aspect had the highest average, followed by the mental aspect and the social relationship aspect. and environmental aspects has the lowest average value, respectively. 2) Guidelines for promoting the development of the quality of life of the elderly of the Ban Lam Nao Subdistrict Administrative Organization. The physical aspect had the highest average level, including staff regularly checking the health of the elderly. There are enough exercise facilities to promote the health of the elderly. Arrange training to provide knowledge about nutrition appropriate to the age of the elderly, followed by mental aspects, including the Subdistrict Administrative Organization providing staff to provide health consultation fees. mind and stress Supporting travel activities outside the area for the elderly. The Subdistrict Administrative Organization arranges for people in the community to participate in taking care of the elderly within the community. and the least is In terms of social relations, the Subdistrict Administrative Organization has supported cultural traditions and organized gatherings, such as the Songkran tradition. Pouring water over the heads of the elderly, the Dhamma Relatives Club, the Elderly Club, etc.